Caracterização dos sistemas de produção leiteiros na região oeste do Paraná por meio de análise multivariada - Defante, Leslié (2011)
In order to characterize the farms, by identifying characteristics of production, milk composition and influence of the management systems of hygiene and sanitary production of milk - SPL of the western region of Paraná State. A study was conducted in 23 SPL, with the collection of data from a semi-structured questionnaire guide and collection of samples of raw milk and cooled water reservoirs.. analyses were performed using physical-chemical (fat, protein, lactose, total solids) of somatic cell counting (SCC) and total bacterial counting (TBC). For microbiological tests were performed to determine the most probable number of total coliform and thermotolerant coliform by multiple tube method. We evaluated the differences found in production systems by means of multivariate statistical techniques, namely: multiple correspondence analysis (MCA), principal component analysis (PCA) and cluster analysis, the milk production and herd feeding management, milking management, reproductive management, disease control, and finally the marketing of milk. The variables that best explained the diversity of the systems were: the amount of milk produced, lactating cows, repetition of estrus, based on feed and milking practices, hygiene and mastitis test ceilings. While the high counts of CBT, CCS and the presence of total coliforms and thermotolerant in some dairy production systems have proved to be indicative of deficiencies in hygiene procedures for milking, cleaning and sanitizing of milking equipment, associated with inadequate cooling of milk. Delivering the decreased concentrations of the components fat, protein and total solids, causing changes in the quality of milk and dairy products. The typology of production systems allowed to portray the diversity in the organization and manner of production, enabling the simplification of the universe of producers, allowing us to tailor production strategies, managing and improving the quality of milk for each system